The using of IFCN’S method in Hungary - Borbély, Csaba; Szabó, Kinga; Csima, Ferenc (Acta Agraria Kaposváriensis, 2006)
The idea of the International Farm Comparison Network (IFCN) was born in Braunschweig, Germany at the Federal Agricultural Research Centre (FAL) in 1997. The program was developed on the basis of the objective to create a unique database updated ever year that makes it possible to compare the economic charachteristics of typical farms operating world wide. The three main goals of IFCN are the following: - to establish and operate a world-wide network dealing with the analysis of agricultural systems, - to analyse and predict the effects of political and technological changes in the participating countries, - to promote contact and change of data between theory and practice. Within the IFCN the basis of the analysis is a simulation model called TIPI-CAL. TIPI-CAL is a recursive-dynamic, production-simulating and accounting model which was developed for farm analysis With the help of the model we can analyse the effects of the change regarding political measures and legal circumstances, which is shown mainly in different management strategies. In relation to this within the European Union adjustment strategies induced by different development processes are of special importance. These processes are analysed both on national and international level thus with individual simulation we can also have some idea about international competitiveness.